2022
DOI: 10.1186/s12884-022-04846-1
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the risk of complications during pregnancy in pregnant women with assisted reproductive technology: a retrospective study using registry linkage from 2013 to 2018 in Shanghai, China

Abstract: Background To evaluate the differences in pregnancy outcomes between assisted reproductive technology (ART) patients and natural pregnant women in Shanghai, China in the past 6 years objectively. And to assess the feasibility of the research method of registry-database linkage in mainland China. Methods This retrospective study was conducted using registry-database linkage. A total of 8102 pregnancies with ART and 8096 parturients with spontaneous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…To date, only few studies have investigated neonatal outcomes in GDM women conceiving with ART. It's known that both ART 25 and GDM 26 may increase the risk of adverse pregnancy outcomes. Aside from the direct effect of multiple pregnancies, the metanalysis of Qin et al 1 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, only few studies have investigated neonatal outcomes in GDM women conceiving with ART. It's known that both ART 25 and GDM 26 may increase the risk of adverse pregnancy outcomes. Aside from the direct effect of multiple pregnancies, the metanalysis of Qin et al 1 .…”
Section: Discussionmentioning
confidence: 99%
“…To only few studies have investigated neonatal outcomes in GDM women conceiving with ART. It's known that both ART 25 and GDM 26 may increase the risk of adverse pregnancy outcomes. Aside from the direct effect of multiple pregnancies, the metanalysis of Qin et al 1 indicated an increased risk of preterm delivery in singleton pregnancies conceived by ART compared to SC(RR 1.71, 95% CI 1.59-1.83).…”
Section: Multivariatementioning
confidence: 99%
“…A series of evidence in recent years suggests frozen embryo transfer could bring better pregnancy outcomes by avoiding excess physiological hormone exposure than fresh embryo transfer ( 25 , 26 ). Although the database does not record the information on transferred embryos, a former cohort study in Shanghai reported that frozen embryo transfer accounted for 68.3% (4,071/5,960) from 2013 to 2018 ( 27 ). A former study compared pregnancy outcomes between different controlled ovulation stimulation protocols in IVF ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…IVF is associated with an increased risk of complications like hypertension, gestational diabetes mellitus, prematurity, and other perinatal complications [ 8 , 9 ]. Hypertension-related complications can affect the mother and the fetus and are observed in 2-3% of pregnancies.…”
Section: Introductionmentioning
confidence: 99%